Future Directions of SROI in Indonesia - Ilham AINUDDIN; Bulan PRABAWANI; Sudharto P. HADI; Fendy E. WAHYUDI (Communications of International Proceedings, 2022)
Social return on investment (SROI) has received increasing attention dari from the Indonesian government , it was included as a new criterion for the Company Performance Rating Program in Environmental Management (PROPER) from the Indonesian Ministry of Environment and Forestry in 2021. Based on a systematic review of the literature that highlights the practice SROI in Indonesia, the purpose of this study is to review existing research related to SROI, the application of SROI in Indonesia and the future direction of the application of SROI in Indonesia. This research is qualitative descriptive analysis and used a systematic literature review with recommended reporting items of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. A qualitative descriptive analysis research taking eight program forms beyond corporate compliance as case studies  and   systematic literature review produced a final data set of 21 studies. The results reveal that The SROI used in Indonesia  dominated by Evaluative SROI which is used to measure or evaluate programs that have been running. Measurements using SROI are able to reveal the success and feasibility of the program well and are needed for the sustainability of the program in the future,but still needs evaluation in several aspects and needs to be further developed In the future, SROI can be further developed in many program.
Keywords: Social Return on Investment; SROI; CSR; Systematic Review.